2022
DOI: 10.1134/s1607672922060114
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA Class I Genotype with Mortality in Patients with Diabetes Mellitus and COVID-19

Abstract: Numerous studies showed that diabetes mellitus (DM) increases the risk of death from COVID-19 by five times. It is generally accepted that the high lethality of COVID-19 against the background of DM is due to the main complications of this disease: micro-and macroangiopathies, as well as heart and kidney failure. In addition, it was shown that acute respiratory viral infection increases the production of interferon gamma, increases muscle resistance to insulin, and modulates the activity of effector CD8+ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The severe infection group in this study was predominantly composed of Hispanic individuals, and this group demonstrated significant changes in immune cell populations and vascular factors which corresponded to a positive correlation with disease severity. As diabetes has been directly linked to increased COVID-19 disease severity [ 46 ], the increased frequency of diabetes, which often leads to complications with viral infections, reported by Hispanic individuals in the severe group offers a prime example of health disparities negatively impacting COVID-19 disease outcomes. Based on these cumulative data, further studies are needed to determine the impact of health disparities on the risk of Hispanic communities developing long COVID.…”
Section: Discussionmentioning
confidence: 99%
“…The severe infection group in this study was predominantly composed of Hispanic individuals, and this group demonstrated significant changes in immune cell populations and vascular factors which corresponded to a positive correlation with disease severity. As diabetes has been directly linked to increased COVID-19 disease severity [ 46 ], the increased frequency of diabetes, which often leads to complications with viral infections, reported by Hispanic individuals in the severe group offers a prime example of health disparities negatively impacting COVID-19 disease outcomes. Based on these cumulative data, further studies are needed to determine the impact of health disparities on the risk of Hispanic communities developing long COVID.…”
Section: Discussionmentioning
confidence: 99%
“…As both groups reported comparable instances of comorbidities, there arises a potential connection between the increased viral burden seen in the severe group and the health disparities suffered by Hispanic populations in Riverside County. As diabetes has been directly linked to increased COVID-19 disease severity [43], the increased frequency of diabetes, which often leads to complications with viral infections, reported by Hispanic individuals in the severe group offers a prime example of health disparities negatively impacting COVID-19 disease outcome in our high-risk population. Severe infection also showed relationships between the comorbidity diabetes and immune and vascular parameters, with diabetic participants exhibiting higher levels of neutrophils, IL-6 and vascular damage-associated myoglobin.…”
Section: Health Disparities and Severity Of Covid-19 Infectionmentioning
confidence: 99%